2020
DOI: 10.1128/aac.02560-19
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Resistance in Clinical Ureaplasma spp. and Mycoplasma hominis and Structural Mechanisms Underlying Quinolone Resistance

Abstract: Antibiotic resistance is a global concern; however, data on antibiotic-resistant Ureaplasma spp. and Mycoplasma hominis are limited in comparison to similar data on other microbes. A total of 492 Ureaplasma spp. and 13 M. hominis strains obtained in Hangzhou, China, in 2018 were subjected to antimicrobial susceptibility testing for levofloxacin, moxifloxacin, erythromycin, clindamycin, and doxycycline using the broth microdilution method. The mechanisms underlying quinolone and macrolide resistance were determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 53 publications
2
32
0
Order By: Relevance
“…Few previous studies have focused on the individual UPA and UUR distributions in clinical Ureaplasma spp. samples (Kawai et al, 2015;Schneider et al, 2015;Yang et al, 2020). In our study, the positive rate of UPA among clinical Ureaplasma spp.…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…Few previous studies have focused on the individual UPA and UUR distributions in clinical Ureaplasma spp. samples (Kawai et al, 2015;Schneider et al, 2015;Yang et al, 2020). In our study, the positive rate of UPA among clinical Ureaplasma spp.…”
Section: Discussionsupporting
confidence: 49%
“…However, in Europe and the United States, the macrolide resistance rates of M. pneumoniae are substantially lower than those in Asia (Waites et al, 2017). Second, these overall figures indicate that resistance rates vary significantly among countries; in some instances, there are even dramatic differences within the same country, which may be related to the different strategy or preference of antimicrobials usage in different areas (Yang et al, 2020). Third, another explanation for this variation may be related to the shortcomings of different Mycoplasma testing kits and the reference broth microdilution method currently used to estimate the antimicrobial susceptibility of Ureaplasma spp.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…At present, these two Mycoplasma can cause pyelonephritis, vaginitis, pelvic inflammation, and other diseases, affecting the quality of life of patients. Therefore, once diagnosed, we must give timely and standardized treatment (5). The results of this study showed that the total infection rate of Mycoplasma in 4082 Chinese patients was 38.39%, mainly due to UU single infection, which was not consistent with the results of some research (6-8), indicating some differences in the distribution of Mycoplasma in different areas, which may be due to the use of antibiotics, sampling sites, detection reagents, and laboratory precision level in different areas.…”
Section: Discussionmentioning
confidence: 99%
“…Considering only studies which used the reliable reference microdilution broth assay from CLSI [93], the rates of levofloxacin-resistant Ureaplasma spp. were 0% between 2007 and 2013 in England and Wales [123], 0.54% between 2017 and 2018 in Wales [124], 1.4% between 2001 and 2006 [125] then 6% between 2015 and 2016 in the USA [126], but 57% between 2007 and 2013 in Japan [127], and 47.5% in 2017-2018 [128] and 84.3% in 2018 in China [129]. Regarding tetracycline resistance, no clinical resistance through the 16S rRNA mutation has been reported in human species and all resistant isolates harbored the tet(M) gene.…”
Section: Prevalence Of Resistance In Ureaplasma Spp and M Hominismentioning
confidence: 92%